2004
DOI: 10.1111/j.1365-2966.2004.07741.x
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the universal radio-X-ray luminosity correlation in black hole candidates

Abstract: In previous work we found that the spectral state switch and other spectral properties of both neutron star (NS) and galactic black hole candidates (GBHC), in low mass x-ray binary systems could be explained by a magnetic propeller effect that requires an intrinsically magnetic central compact object. In later work we showed that intrinsically magnetic GBHC could be easily accommodated by general relativity in terms of magnetospheric eternally collapsing objects (MECO), with lifetimes greater than a Hubble tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…A similar correlation was subsequently also seen in V404 Cyg (also in the low-hard state), which led to the claim that the correlation is the same for all microquasars (Gallo et al 2003). If proven, such a universal radio/X-ray correlation would have profound implications on theoretical models (e.g., Heinz 2004;Robertson & Leiter 2004;. However, as noted by Xue et al (2006), the data shown by Gallo et al (2003) are dominated by only two sources (GX 339−4 and V404 Cyg); the data points for other sources are very limited in their dynamical ranges yet already show significant deviations from the universal correlation.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…A similar correlation was subsequently also seen in V404 Cyg (also in the low-hard state), which led to the claim that the correlation is the same for all microquasars (Gallo et al 2003). If proven, such a universal radio/X-ray correlation would have profound implications on theoretical models (e.g., Heinz 2004;Robertson & Leiter 2004;. However, as noted by Xue et al (2006), the data shown by Gallo et al (2003) are dominated by only two sources (GX 339−4 and V404 Cyg); the data points for other sources are very limited in their dynamical ranges yet already show significant deviations from the universal correlation.…”
Section: Introductionmentioning
confidence: 90%
“…For microquasars, such a jet-accretion coupling might manifest itself in the correlated radio and X-ray variabilities (Robertson & Leiter 2004;. Indeed, a positive radio/X-ray correlation was first established for GX 339−4 in the low-hard state .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Indeed, there are now strong evidences that the so-called astrophysical BH candidates are ultramagnetized ultrahot ultracompact objects rather than cold, dead, nonmagnetized true BHs. [55][56][57][58][59][60][61] And the claim of precise detection of the spin of a Kerr BH 62 must actually mean detection of spinning MECOs because true mathematical Kerr BHs have zero mass, zero rotation parameter (a = M = 0). 19,20 So finite mass BHs as well as all gravitational singularizes (like "Big Bang") could be illusions created by simplistic mathematical exercises and "exact solutions" which ignore all complexities of the throbbing, evolving and interacting gravitating objects in the real universe.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the massive compact BH candidates cannot be true BHs. Indeed there are significant amount of observational evidences, that the so-called BH candidates could be ultracompact, ultramagnetized, ultrahot balls of plasma [49][50][51][52][53][54][55]. Recall that the Sun too is a magnetized plasma and the violent eruptions like Coronal Mass Ejection (CME) could be traced to such magnetized plasma ativities.…”
Section: Discussionmentioning
confidence: 99%